Neo traditional boutique hotel - Yusof, Zeenat Begam; Yusof, Fatin Nabila (2019)
Tourism cities are facing massive emergence of new tourism enterprises that continuously catering the changing needs and lifestyles of tourists and local communities. Hospitality industry plays a major role in ‘branding’ tourism cities However, the current issue on overdevelopment of tourism accommodations with similar branding approach are causing many cities in the world losing their creativeness (Chang and Teo, 2008). The similar issue also occurred in Malaysia especially in Melaka city where thousands of hotels emerged around the cities without having creative branding style (Hall, 2000). Therefore, the need of themed boutique hotels is vital to attract local and international tourists to Melaka city. Consequently, a Neo Traditional Boutique Hotel was proposed which have not more than 10 rooms, maximum of 2-storey height with other supporting facilities. The Boutique hotel was proposed to be located at Jalan Klebang Besar near Bert’s garden restaurant.